(untitled) (Atti del Sodalizio Glottologico Milanese, 2014)
This paper analyzes the genre of some Early New High German travel books. At first those texts are interesting on a cultural, historical and economical point of view, among Germans, Italians (Venetian especially) and various people of the Near East. The interest is obviously also linguistic. The most important texts are of the XV century. They are described and analyzed, with particular emphasys on the linguistic aspects, of which they reveal themselves to be extremely rich: proper names, toponyms, phenomena of linguistic contact. The texts are also described in light of their diatextual properties. The texts are thus an highly important source to understand the formation of the (Early) New German. KEYWORDS: Early New High German, travel books, text analysis, text linguistics, linguistic contact